Extraction of non-ferrous metals and rhenium from lead dusts of copper production - Baigenzhenov, O.S.; Akkenzheyeva, A.; Turkmenbayeva, M.; Kizdarbekova, M.; Turan, M.D. (Rasayan Journal of Chemistry, c/o Dr. Pratima Sharma, 2021)
The recovery of copper, zinc and rhenium from copper melting dust was investigated using the two-step leaching method. The effects of leaching parameters such as leaching time, liquid/solid ratio, leaching temperature and hydrogen peroxide concentration were studied. Experiments were performed in two stages (1) recovery of copper and zinc, and (2) recovery of rhenium. The optimum leaching conditions for copper and zinc were found as follows: leaching time is 60 min; H2SO4 concentration 80 g/L; liquid/solid ratio is 3.0; leaching temperature is 80 °C. Under these conditions, copper and zinc recovering yields were obtained at 90.5% and 92.5%, respectively. Optimum leaching conditions for rhenium were also achieved as follows: leaching time is 90 min; liquid/solid ratio is 3.0 mL/g leaching temperature is 70 °C; and hydrogen peroxide concentration is 3.0 %. More than 97 % Re was recovered under optimum leaching conditions of rhenium. © 2021, Rasayan Journal of Chemistry, c/o Dr. Pratima Sharma. All rights reserved.
Keywords: Copper; Leaching; Lead dusts; Rhenium; Zinc